AN ANALYSIS OF TRANSLATION SHIFTS IN THE INDONESIAN TRANSLATION OF TOWARDS ZERO - Aswarini Sentana (Jurnal Sosial Humaniora dan Pendidikan, 2022)
This is linguistic research of translation that presents an analysis of translation shifts in the novel entitled “Menuju Titik Nol,” which is the Indonesian translation of an English novel “Towards Zero.” The purpose of this research is to find out the types of translation shifts and the most frequent type of translation shifts that occur in the translation. The method that is used in this research is a descriptive qualitative research method. From the translation, the researcher takes the first 100 data of translation shifts and then analyzes the data to identify the types and the most frequent translation shifts in the target text using related translation shifts theories. The results of this research show that the types of shifts found in the Indonesian translation of Towards Zero are level shifts and all types of category shifts, which are structure shifts, class shifts, unit shifts, and intra-system shifts. The occurrence of all types of translation shifts in the translation is due to the difference in some linguistic systems of both languages. The most frequent shifts that occur in the translation is structure shifts. The structure shifts are found in the translation of noun phrases and the translation of active sentences into passive or vice versa.